A Visual Identity Design of Trio Jaya Bidaran & Ciput Cake in Blitar City - Ayun, Qurrota; Costa Rica El Chidtian, Aileena Solicitor; Wulandari, Sri (VCD, 2024)
The UMKM that we chose is the business of making Bidaran and Ciput cakes "Bidaran & Ciput Trio Jaya Cake" located in Pakunden Village, Kec. Sukorejo, Blitar City. This Bidaran & Ciput Trio Jaya cake has a prominent uniqueness, namely many flavors, but the development of this business is constrained by not having a brand that is the hallmark of the business and lack of knowledge about digital marketing. The solution is to make innovations in product Visual Identity to make it more attractive and to carry out marketing development by creating social media accounts so that these UMKM can be widely known so that they can help business development.